(untitled) (Jurnal Bina Praja, 2017)
Jakarta is one of the areas with high urbanization number and its impacts, so it requires Local Government to control the urbanization to minimize its negative impacts. On the other hand, the rights to freedom of movement and residence throughout the territory of Indonesia are guaranteed by the Law. So, this study becomes important to know how the efforts of Jakarta Provincial Government to control the urbanization as seen in human rights perspective. This study uses a qualitative approach and descriptive method. This paper argues that the urbanization control by Jakarta Local Government with orderly administration approach is not effective to control the urbanization and only created constraints of people movement and this policy violates the right to freedom movement and residence. It further suggests that the orderly administration approach should be replaced by the human rights approach in controlling the urbanization in Jakarta if it is to seek better policy.